試論儒家倫理對構建當代生命科技倫理的價值: The Construction of Contemporary Science and Technology Ethics: A Confucian Perspective - SHEN, Xiuqin; YANG, Tongwei (International Journal of Chinese & Comparative Philosophy of Medicine, 2008)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 20 世紀末生命科技的迅速發展，對傳統的倫理觀念帶來了巨大的衝擊，引發了很多棘手的倫理問題。為了解決這些問題，構建適應生命科技發展的倫理體系不僅非常必要，而且異常迫切。很多學者都認為儒家倫理與生命科技倫理要求相悖。但筆者認為，儒家倫理思想中的 “仁愛”、“己所不欲，勿施於人”以及“天人合一”等寶貴的思想資源對當今生命科技倫理構建是有著重要價值的。因此，本文試圖充分挖掘傳統儒家倫理中的優勢資源，探討儒家倫理對現代生命科技倫理構建有益的幾個基本理念以及對和諧人與人之間，人與社會之間以及人與自然之間的價值所在，以發揮其對當代生命科技倫理構建的引導作用。 We live in an age of unprecedented human mastery — over birth and death, body and mind, nature and human nature. The rapid pace of scientific and technological development is not always matched by the ethical considerations within wider society on the impacts of such development. Very often, technological progress such as organ transplants and genetic engineering is not always ethically acceptable. Meanwhile, traditional ethical values also face great challenges. Contemporary science and technology ethics re-examines the ethical issues by which we live and ask the question: do we have in place the ethical guidelines through which we can incorporate these developments with the minimum of disruption and disaffection? This paper attempts to address the science and technology ethics with the framework of Confucianism. Some Chinese scholars tend to hold the view that Confucianism is incompatible with the contemporary discourse in terms of bioscience, biotechnology and bioethics. We shall then argue that we should employ the existing ethical systems, Confucianism for example, to approach the problems, and thus come up with a new perspective to look at technological applications in terms of engineering processes and products, bioethics and informatics, and our environmental responsibilities. The Confucian life philosophy in terms of “benevolence,”“ respecting life,” and the“ unity of heaven and humans” will redirect our attention from purely human-centered interests to a more balanced concern via a harmony between self and other, humans and nature. DOWNLOAD HISTORY | This article has been downloaded 378 times in Digital Commons before migrating into this platform.